The Hidden Strains of ‘Cool’ Jobs - Delgaty, Aaron; Wilson, Eli R (Sociology (Oxford), 2024)
A growing number of workers today are drawn to jobs that offer symbolic and cultural rewards but not necessarily stable employment or livable wages. Existing literature posits the exploitative nature of this labor arrangement, where workers must weigh the ‘cool’ aspects of their jobs against other less desirable aspects. Yet what happens when both these dimensions of work are deeply intertwined and subject to changing perspectives? Drawing on ethnographic data and in-depth interviews with US craft beer workers, we show how ‘cool’ aspects of brewery jobs are experienced as significant sources of material, social, and work identity strain that cause some workers to grow estranged from their jobs over time. We suggest a broader framework for understanding the hidden strains of jobs that appeal to workers for symbolic reasons, and advocate for shifting jobs in the new economy away from cool-yet-precarious employment bargains and toward more sustainable forms of employment.